An empirical study of the antecedents and consequences of brand engagement. Issue 4 (1st June 2015) - Wong, Ho Yin; Merrilees, Bill
Abstract : Purpose: – The purpose of this paper is to develop and empirically test a model of brand engagement. More specifically, the aim is to evaluate both antecedents and consequences of brand engagement, from a management perspective. Design/methodology/approach: – A quantitative survey of 403 firms is undertaken to test the model. Structural equation modelling (SEM) is used to estimate the parameters of the model. Findings: – A reliable and valid measure of brand engagement is established. The SEM model works well, in terms of goodness of fit indices. The results demonstrate that there are major brand performance benefits (consequences) of brand engagement. Additionally, and important for the practical implications, the results show that brand orientation is a major antecedent to brand engagement. Research limitations/implications: – The study needs to be replicated in other countries, with scope to add other explanatory variables for influencing brand engagement. The results have considerable practical benefits for guiding the introduction of measures to enhance brand engagement. Originality/value: – The study builds on earlier (mainly consumer) conceptual approaches to brand engagement, but goes further in that it provides empirical evidence about the nature, antecedents and consequences of brand engagement and further, offers a management rather than consumer perspective. Essentially, the study reveals a new perspective of factors that encourage firms to connect/engage their brands with consumers. Brand engagement is a dual concept, reflecting both a consumer and a firm perspective.